IDENTIFIKASI TARGET KHALAYAK RADIO SUARA SURABAYA DI MEDIA SOSIAL - Ester Krisnawati; Pratiwi Cristin Harnita (Universitas Kristen Satya Wacana, 2018)
The broadcasting world began to experience many changes along with the presence of new media until it led to media convergence. The phenomenon of convergence has brought many mass media to begin convergence to stay alive amid increasingly fierce media competition, one of which is Radio Suara Surabaya. This study aims to identify the target audience of Radio Suara Surabaya in social media that is Facebook, so that it can be known the suitability of the desired target audience, as well as to determine the extent of the contribution of social media that exists in meeting the information needs of the audience, especially young people. In this study, researchers used a qualitative research approach to the type of descriptive research. The results of this study explain that E100 is one of the media from Radio Suara Surabaya to target young people. The position of the E100 does not replace the presence of Radio Suara Surabaya but rather becomes a complementary medium for obtaining information. Through this E100, Radio Surabaya is trying to target generations